Two Cases of Non-Radial Filament Eruption and Associated CME Deflection - Kostadinka Koleva; Ramesh Chandra; Pooja Devi; Peter Duchlev; Momchil Dechev (Universe, 2025)
The purpose of this paper is to analyze the multi-wavelength and multi-instrument observations of two quiescent filament eruptions as well as the deflection of associated CMEs from the radial direction. The events occurred on 18 October 2017 and 9 May 2021, respectively, in the southern solar hemisphere. Both of them and associated flares were registered by the Atmospheric Imaging Assembly (AIA) aboard the Solar Dynamics Observatory (SDO) and the Solar Terrestrial Relations Observatory–Ahead (STEREO A) Observatory in different EUV wavebands. Using data from STEREO A COR1 and COR2 instruments and the Large Angle and Spectrometric Coronagraph (LASCO) onboard the Solar and Heliospheric Observatory (SOHO), we investigated morphology and kinematics of the eruptions and the latitudinal offset of the related CMEs with respect to the erupting filaments. Our observations provide the evidence that the two filament eruptions were highly non-radial. The observed deviations are attributed to the presence of low-latitude coronal holes.